Implementing a Democratic Attitude in the Physical Education Learning System - Alfredo Mahesa Putra; Chairul Rachmat Shiddiq Nata Prawira; Ferdi Yusuf Triyanto; Zaki Abdul Aziz; Intan Purwitasari; Mochamad Whilky Rizkyanfi (Jurnal Pendidikan Jasmani (JPJ), 2023)
There are still learning conditions in indonesia that have not implemented a democratic attitude in physical education. The factor that causes this problem is the lack of communication between teachers and students. The aim of this research is to see the extent of closeness between teachers and students in physical education. A qualitative approach with a survey method was used by researchers to determine the performance of physical education teachers through students with a number of resource persons from various sources. This research was conducted at the Indonesian Education University by asking students to become resource persons with the aim of finding out what the democratic attitude towards physical education learning was while they were still there. high school. The technique used to collect data is interviews, resource persons are asked to answer 5 questions given by the examiner. The method used in this research is the method qualitative. The results of the research show that some teachers have not implemented a democratic attitude. Based on the research findings, it can be concluded that there is still a lack of full implementation of democratic attitudes in physical education lessons. Field observations are necessary for future study in order to observe directly how democratic attitudes are implemented in physical education instruction.